KIR2DL5B and HLA DRB1*12 alleles seems to be associated with protection against HIV‐1 in serodiscordant couples in Burkina Faso. Issue 9 (12th May 2022) - Lallogo, Tatiana Doriane; Djigma, Florencia W.; Sorgho, Pegdwendé Abel; Martinson, Jeremy James; Compaore, Tégwindé Rebeca; Traore, Lassina; Bado, Prosper; Bazie, Bapio Valérie Elvira Jean Télesphore; Amegnona, Lanyo Jospin; Kagone, Thérèse S.; Ouedraogo, Rogomenoma Alice; Ilboudo, Denise P.; et al.
Abstract: The human immunodeficiency virus (HIV) belongs to the Retroviridae family and remains a public health problem in sub‐Saharan Africa. Recent reports from WHO have shown that 33 million people died from HIV infections. HIV is one of the most serious fatal human diseases of the 20th and 21st centuries. However, variations in genetic and immunological factors are associated with protection against HIV infection in uninfected people exposed to HIV. This is the case with naturals killers which play an important role in the progression or regression of HIV infection. The objective of this study is to characterize certain HLA (human leukocyte antigen) class II genes and KIR genes in HIV‐1 serodiscordant couples in Burkina Faso. This study was carried out at Burkina Faso among nineteen (19) HIV‐1 serodiscordant couples. Classical multiplex PCR (SSP‐PCR) was used to characterize the presence or absence of the KIR genes and certain class II HLAs ( DRB1*11 and DRB1*12 ). The characterization of the KIR and HLA genes DRB1*11, DRB1*12 in this study demonstrated that the inhibitor KIR2DL5B, would confer protection against HIV‐1 infection in seronegative partners (odd ratio [OR] = 0.13 [0.02−0.72] and p = 0.029), and the HLA DRB1*12 allele was associated with protection against HIV‐1 infection in seronegative partners (OR = 0.16 [0.03−0.77] and p = 0.038). AA and Bx haplotypes were not found to be associated with HIV‐1 infection in serodiscordant couples. This study confirms the involvement of the KIR genes in viral pathologies such as HIV‐1 infection. Future larger‐scale studies may provide a better understanding of the molecular mechanism by which the KIR haplotype and combination of KIR/HLA are associated with protection against HIV infection.